2023
DOI: 10.1136/archdischild-2022-324612
|View full text |Cite
|
Sign up to set email alerts
|

Antiseizure medication at discharge in infants with hypoxic-ischaemic encephalopathy: an observational study

Abstract: ObjectivesTo assess variability in continuation of antiseizure medication (ASM) at discharge and to evaluate if continuation of ASM at discharge is associated with death or disability among infants with hypoxic-ischaemic encephalopathy (HIE) and seizures.DesignRetrospective study of infants enrolled in three National Institute of Child Health and Human Development Neonatal Research Network Trials of therapeutic hypothermia.Setting22 US centres.PatientsInfants with HIE who survived to discharge and had clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Previous studies have shown variation by center in the percent of infants with acute symptomatic seizures discharged on ASM. (10,17,18) Historically our academic provider group working in three local hospitals, or has had a high proportion of infants with seizures discharged on ASM. This was compounded by challenges in obtaining neurology follow-up in a timely manner after discharge, resulting in infants being exposed to prolonged duration of ASM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown variation by center in the percent of infants with acute symptomatic seizures discharged on ASM. (10,17,18) Historically our academic provider group working in three local hospitals, or has had a high proportion of infants with seizures discharged on ASM. This was compounded by challenges in obtaining neurology follow-up in a timely manner after discharge, resulting in infants being exposed to prolonged duration of ASM.…”
Section: Discussionmentioning
confidence: 99%
“…(4-9) Continuation of ASM at discharge may be associated with increased neurodevelopmental impairment. (10) While higher than the average population, epilepsy risk in neonates following acute symptomatic seizures remains relatively low and seizures often do not present until months to years after discharge. (11)(12)(13) Continuation of ASM after discharge does not decrease the risk of epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Sewell et al , on behalf of the Eunice Kennedy Shriver National Institute of Child Health and Human Development, provide more evidence on the enormous variation in practice that exists for these infants, with an observational study on antiseizure medication (ASM) use after discharge for infants with hypoxic-ischaemic encephalopathy (HIE) 1. The data were collected on infants who had been enrolled into various cooling trials over the preceding 15 years.…”
mentioning
confidence: 99%
“…The conclusion was that discontinuation of ASM at hospital discharge was safe. Of course, the results of this study could not have influenced the results of Sewell et al ,1 as their data were retrieved from randomised controlled trials (RCTs) conducted over the previous decade. While no data were available on which ASM was employed, it would be reasonable to conclude that this was phenobarbital for the majority, as was the case in the previous study 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation